Expecting penises in Chatroulette: Race, gender, and sexuality in anonymous online spaces. (3rd April 2017) - Korn, Jenny Ungbha
ABSTRACT: As a femme woman of color, I employ critical autoethnography based on my participant observation within Chatroulette for a qualitative study on how online impressions through web cameras with strangers are formed in quick bursts of time. Chatroulette's anonymity adds interesting context for impression creation in an online environment that emphasizes ocularcentrism of the embodied self. This article adds to methodologies of self-care for the qualitative researcher by positioning the issue of self-care in the online field, where "regular" interactions based on race, gender, sexuality, and more may leave autoethnographers from marginalized communities especially vulnerable. This study complicates the conceptual boundaries of "audience, " "participation, " and "observation" for online autoethnographic research. This research contributes to impression formation theory by focusing on the importance of the body in immediate, one-time impression constructions with conversational partners online. Race, gender, and sexuality impact online communication, even when a word is not even said.